Palladium-catalysed cyclisation of alkenols: Synthesis of oxaheterocycles as core intermediates of natural compounds - Palík, Miroslav; Kožíšek, Jozef; Koóš, Peter; Gracza, Tibor (Beilstein Journal of Organic Chemistry, 2014)
The study of Pd-catalysed cyclisation reactions of alkenols using different catalytic systems is reported. These transformations affect the stereoselective construction of mono- and/or bicyclic oxaheterocyclic derivatives depending on a starting alkenol. The substrate scope and proposed mechanism of Pd-catalysed cyclisation reactions are also discussed. Moreover, the diastereoselective Pd-catalysed cyclisation of appropriate alkenols to tetrahydrofurans and subsequent cyclisation provided properly substituted 2,5-dioxabicyclo[2.2.1]heptane and 2,6-dioxabicyclo[3.2.1]octane, respectively. Such bicyclic ring subunits are found in many natural products including ocellenynes and aurovertines.
Keywords: alkenols; cycloetherification; homogeneous catalysis; natural products; palladium

(untitled) - Gracza, T.; Jäger, V. (Synlett, 1992)

(untitled) - Cao, S.-G.; Wu, X.-H.; Sim, K.-Y.; Tan, B. K. H.; Pereira, J. T.; Goh, S.-H. (Tetrahedron, 1998)

(untitled) - Malmstrøm, J.; Christophersen, C.; Barrero, A. F.; Oltra, J. E.; Justicia, J.; Rosales, A. (J. Nat. Prod., 2002)

(untitled) - Howard, B. H.; Raistrick, H. (Biochem. J., 1949)

(untitled) - Beutler, J. A.; Hilton, B. D.; Clark, P.; Tempesta, M. S.; Corley, D. G. (J. Nat. Prod., 1988)

(untitled) - Schulte, G. R.; Chung, M. C. H.; Scheuer, P. J. (J. Org. Chem., 1981)

(untitled) - Wright, A. D.; König, G. M.; de Nys, R.; Sticher, O. (J. Nat. Prod., 1993)

(untitled) - Jansen, R.; Wray, V.; Irschik, H.; Reichenbach, H.; Höfle, G. (Tetrahedron Lett., 1985)

(untitled) - Baldwin, C. L.; Weaver, L. C.; Brooker, R. M.; Jacobsen, T. N.; Osborne, C. E., Jr; Nash, H. A. (Lloydia, 1964)

(untitled) - Osselton, M. D.; Baum, H.; Beechey, R. B. (Biochem. Soc. Trans., 1974)

(untitled) - Mulheirn, L. J.; Beechey, R. B.; Leworthy, D. P.; Osselton, M. D. (J. Chem. Soc., Chem. Commun., 1974)

(untitled) - Wang, F.; Luo, D.-Q.; Liu, J.-K. (J. Antibiot., 2005)

(untitled) - Lai, S.; Matsunaga, K.; Shizuri, Y.; Yamamura, S. (Tetrahedron Lett., 1990)

(untitled) - Cardillo, G.; Orena, M. (Tetrahedron, 1990)

Houben-Weyl - Cardillo, G.; Orena, M. (Formation of C–O bonds by cyclization onto olefinic double bonds forming lactones and ethers, 1995)

Synthesis of Heterocycles via Metal-Catalyzed Reactions that Generate One or More Carbon-Heteroatom Bonds - Wolfe, J. P. (Synthesis of saturated heterocycles via metal-catalyzed alkene carboamination or carboalkoxylation reactions, 2013)

(untitled) - Wolfe, J. P. (Eur. J. Org. Chem., 2007)

(untitled) - Wolfe, J. P. (Synlett, 2008)

Stereoselective Synthesis of Drugs and Natural Products - Gracza, T. (Intramolecular oxycarbonylation in stereoselective synthesis, 2013)

(untitled) - Doháňošová, J.; Gracza, T. (Molecules, 2013)

(untitled) - Muzart, J. (J. Mol. Catal. A: Chem., 2010)

(untitled) - Babjak, M.; Remeň, L.; Szolcsányi, P.; Zálupský, P.; Mikloš, D.; Gracza, T. (J. Organomet. Chem., 2006)

(untitled) - Babjak, M.; Remeň, L.; Karlubíková, O.; Gracza, T. (Synlett, 2005)

(untitled) - Palík, M.; Karlubíková, O.; Lásiková, A.; Kožíšek, J.; Gracza, T. (Eur. J. Org. Chem., 2009)

(untitled) - Palík, M.; Karlubíková, O.; Lackovičová, D.; Lásiková, A.; Gracza, T. (Tetrahedron, 2010)

(untitled) - Bravo, F.; Kassou, M.; Castillón, S. (Tetrahedron Lett., 1999)

(untitled) - Fürstner, A.; Jumbam, D.; Teslic, J.; Weidmann, H. (J. Org. Chem., 1991)

(untitled) - Koppenhoefer, B.; Walser, M.; Schröter, D.; Häfele, B.; Jäger, V. (Tetrahedron, 1987)

(untitled) - Jäger, V.; Schröter, D.; Koppenhoefer, B. (Tetrahedron, 1991)

(untitled) - Babjak, M.; Zálupský, P.; Gracza, T. (ARKIVOC, 2005)

(untitled) - Sánches-Sancho, F.; Valverde, S.; Herradón, B. (Tetrahedron: Asymmetry, 1996)

(untitled) - Chandrasekhar, S.; Parida, B. B.; Rambabu, C. (J. Org. Chem., 2008)

(untitled) - Jiao, P.; Kawasaki, M.; Yamamoto, H. (Angew. Chem., Int. Ed., 2009)

(untitled) - Prat, I.; Font, D.; Company, A.; Junge, K.; Ribas, X.; Beller, M.; Costas, M. (Adv. Synth. Catal., 2013)

(untitled) - Jarosz, S.; Skóra, S.; Szewczyk, K. (Tetrahedron: Asymmetry, 2000)

(untitled) - Trost, B. M.; Tenaglia, A. (Tetrahedron Lett., 1988)

(untitled) - Passiniemi, M.; Koskinen, A. M. P. (Tetrahedron Lett., 2008)

(untitled) - Roulland, E. (Angew. Chem., Int. Ed., 2008)

(untitled) - Uenishi, J.; Ohmi, M.; Ueda, A. (Tetrahedron: Asymmetry, 2005)

(untitled) - Uenishi, J.; Ohmi, M. (Angew. Chem., Int. Ed., 2005)

(untitled) - Kawai, N.; Lagrange, J.-M.; Ohmi, M.; Uenishi, J. (J. Org. Chem., 2006)

(untitled) - Kawai, N.; Lagrange, J.-M.; Uenishi, J. (Eur. J. Org. Chem., 2007)

(untitled) - Kawai, N.; Hande, S. M.; Uenishi, J. (Tetrahedron, 2007)

(untitled) - Wolfe, J. P.; Rossi, M. A. (J. Am. Chem. Soc., 2004)

(untitled) - Hay, M. B.; Hardin, A. R.; Wolfe, J. P. (J. Org. Chem., 2005)

(untitled) - Hay, M. B.; Wolfe, J. P. (J. Am. Chem. Soc., 2005)

(untitled) - Hay, M. B.; Wolfe, J. P. (Tetrahedron Lett., 2006)

(untitled) - Ward, A. F.; Wolfe, J. P. (Org. Lett., 2010)

(untitled) - Chamberlin, A. R.; Mulholland, R. L., Jr; Kahn, S. D.; Hehre, W. J. (J. Am. Chem. Soc., 1987)

(untitled) - Kahn, S. D.; Hehre, W. J. (J. Am. Chem. Soc., 1987)

(untitled) - Muñiz, K. (Angew. Chem., Int. Ed., 2009)

(untitled) - Xu, L.-M.; Li, B.-J.; Yang, Z.; Shi, Z.-J. (Chem. Soc. Rev., 2010)